ANALISIS PRAKTIK PENGUNGKAPAN INTELLECTUAL CAPITAL STUDI PADA PERUSAHAAN SUB SEKTOR INDUSTRI OTOMOTIF - Masiyah Kholmi; Endang Dwi Wahyuni; Febri Heni (Universitas Muhammadiyah Malang, 2020)
The aim of this study is to analyze the intellectual capital disclosure practices by Indonesian automotive industry. Content analysis was used to analyze the annual report for one the year 2016. This research used Guthrie at., el. scheme of intellectual capital components. In this scheme, IC was categorized into 3 groups; relational competence (human capital: 8th items).internal structures (organizational capital: 15th items); and external structures (customer/relational capital: 13th items); The result shows that percentage of IC disclosure by Indonesian automotive industry was high relatively In 2016, there were some attributes that not disclosed yet by a company, it was ’copyright’. There was no company that discloses all of the 36th components of IC in their annual report. The maximum number of the attribute that disclosed by a company was 31.